Developing leadership in women's health research. Issue 3 (25th June 2020) - Bogner, Hillary R.; Abbuhl, Stephanie; Tuton, Lucy Wolf; Dougherty, Bridget; Zarowin, Diana; Guevara, Alejandra; McClintock, Heather
Abstract : Purpose: Recruiting medical students into women's health and gender-based medical research is important internationally. Medical student research training is critical for developing future women's health leaders who are adept at conducting high-impact research. This paper aims to describe a six-month medical student research fellowship in women's health in terms of fellowship recipients' publications related to their research project and future academic careers. Design/methodology/approach: Targeted searches of fellowship recipients and their fellowship mentors were conducted in PubMed and Scopus from 2001–2017. Prior student fellows were also e-mailed and called to assess whether they held academic positions. Findings: Since 2001, funds have been secured to support a total of 83 students (69 women, 14 men) in a mentored research experience in women's health and gender-based medicine. In total, 48 out of the 83 (57.8%) medical student fellowship recipients published at least one peer-reviewed research paper or scientific review related to their research project. Of the 50 prior recipients with a least five years of follow-up data (41 women, 9 men), 26 (52%) were in academic careers. Research limitations/implications: Because this is an observational study and only medical students interested in women's health applied to be a student fellow, there is an inability to infer causality. Practical implications: Following completion of the medical student research training fellowship in women's health, more than half of recipients published in peer-reviewed medical journals on their research project. Originality/value: This study explores the association of an innovative medical student experience in women's health research on subsequent fellowship-related publications and career outcomes, contributing to the body of knowledge on the influence of a mentored research leadership program for medical students on academic professional development.